Investigating Affective Responses to Remotely Delivered “At Home” Low Volume High Intensity Interval Exercise: A Non-Randomized Parallel Group Feasibility Study - Howard, Imogen; Niven, Ailsa; Kelly, Paul; Phillips, Shaun M. (Frontiers in Sports and Active Living, 2022)
Background: Low volume-high intensity interval exercise (LV-HIIE) has gained interest, due to its efficiency for invoking health and fitness benefits. However, little research has studied ‘at home’ feasibility or effects of LV-HIIE. This study aimed to demonstrate that remote ‘at-home’ LV-HIIE research is possible, and investigate if affective responses to the LV-HIIE protocol, subsequent intentions and self-efficacy to repeat were related to self-reported tolerance of the intensity of exercise. Methods: Using self-reported tolerance of the intensity of exercise, participants were divided into low tolerance (LT, n = 14), middle tolerance (MT, n = 15), and high tolerance (HT, n = 12) groups. Participants completed a 20-minute LV-HIIE circuit training video (2 x (10x30s work, 15s rest)) at home. Participants reported ratings of perceived exertion, affective valence, and perceived activation at baseline, during the protocol, immediately post-protocol, and during the cool down. 20-minutes after completion, respondents answered questions on exercise task self-efficacy and intentions to repeat LV-HIIE. Results: The study recruited n=65 individuals, of whom n=50 passed screening. Ultimately n=41 (82%) completed the exercise protocol and data collection. Ratings of perceived exertion were not significantly different between groups (P = 0.56), indicating similar perceptions of task difficulty. There was no significant effect of tolerance on affective valence (P = 0.36) or felt arousal (P=0.06). There was evidence of high individual variability in affective responses within and between participants. Subsequent intentions and self-efficacy to repeat the exercise protocol did not seem to be related to affective valence during or after the protocol. Discussion: Recruitment and data collection indicated that research into ‘at home’ LV-HEII is possible. High individual differences on affective responses suggest that LV-HEII may be appropriate for some but not all as an exercise option. Assessing self-reported tolerance of intensity of exercise may not appropriately identify whether or not LV-HIIE will be appropriate for an individual.